Genotype-environment interaction in evaluating yielding of selected edible potato*(Solanum tuberosum L.) cultivars - Rymuza, Katarzyna; Bombik, Antoni (Plant Breeding and Seed Science, 2010)
In the research carried out in the years 1999-2001 the following characteristics of three edible potato cultivars were determined: tuber yield, starch content, dry matter content, vitamin C content and starch yield. Genotype-environment interaction for the above characteristics was evaluated on the basis of main effects (genotypes and years) and interaction effects by means of the variance analysis for repeated experiments and according to the linear model for the design which confounds the type 33 interaction. Moreover, there were calculated the variance of genotype stability describing the environmental variation of the genotypes, and the ecovalence coefficient which describes the genotype x environment interaction. All the analysed characteristics were influenced by the cultivars (genotypes) and the environment. The genotype-environment interaction reflecting different response of the cultivars to changeable environmental conditions proved to be significant for all the examined characteristics. The analysis of results does not allow to unambiguously indicate the stabile genotype because the Muza cultivar was most stable for vitamin C and dry matter contents, and starch yield whereas Aster and Ania proved to be most stable as far as tuber yield and starch content, respectively, were concerned...